Hyperpigmentation: from the past to the future. Review of reports - Board Editorial (ZAO "Consilium Medicum", 2024)
During the Pigmentation as an Urgent Problem of the XXI Century. Traditions and Innovations and Pigmentation: A Specialist's View research and practical conferences, leading experts in the field of dermatovenereology and cosmetology presented their reports and discussed global trends in the treatment of hyperpigmentation. The authors presented new data on cosmetic products and patient management approaches.